1989
DOI: 10.1083/jcb.108.6.2519
|View full text |Cite
|
Sign up to set email alerts
|

Differential structural requirements for fibrinogen binding to platelets and to endothelial cells.

Abstract: Abstract. The cytoadhesins represent a group of RGD receptors that belongs to the integrin superfamily of adhesion molecules. Members of this cytoadhesin family include the platelet GPIIb-IIIa and the vitronectin receptors. These glycoproteins share the same/~-subunit, which is associated with different ot subunits to form an a/[3 heterodimer. In the present study, we have analyzed the fine recognition specificity of the cytoadhesins from platelets and endothelial cells for the adhesive protein, fibrinogen. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 54 publications
4
31
0
Order By: Relevance
“…It has been shown that Phe (F) as a hydrophobic binding element following the RGD sequence further enhances activity, therefore RGDF has been used as lead sequence in all of the peptides. This is in accordance with the general finding that the antiaggregatory activity of peptides following the sequence pattern RGDX decreases in the following series for X = F > V > C > Q > S [36].…”
Section: Designsupporting
confidence: 79%
“…It has been shown that Phe (F) as a hydrophobic binding element following the RGD sequence further enhances activity, therefore RGDF has been used as lead sequence in all of the peptides. This is in accordance with the general finding that the antiaggregatory activity of peptides following the sequence pattern RGDX decreases in the following series for X = F > V > C > Q > S [36].…”
Section: Designsupporting
confidence: 79%
“…Gel-filtered human platelets were suspended in Tyrode's buffer containing 1 mM Ca 2ϩ to a final concentration of 3 ϫ 10 8 per ml (13). Peptides were then added to the platelets up to 50 M for a 30-min incubation at 22°C, together with 300 nM 125 I-labeled fibrinogen.…”
Section: Methodsmentioning
confidence: 99%
“…The platelets were then stimulated with either 10 M ADP͞20 M epinephrine or 50 M thrombin receptor agonist peptide. After 15 min, 125 Ifibrinogen binding was measured as described (13,14). lacking the transmembrane and cytoplasmic tails of both subunits, was performed by using an immunocapture assay similar to that described (16).…”
Section: Methodsmentioning
confidence: 99%
“…It is also established that the amino acid adjacent to the C-terminus of short RGD peptides alters its affinity to ¢xlIb[~3 integrin, with tryptophan and phenylalanine increasing its affinity and hydrophilic amino acids decreasing its affinity [2].…”
Section: Introductionmentioning
confidence: 99%